2015
DOI: 10.1002/biof.1215
|View full text |Cite
|
Sign up to set email alerts
|

The changes in bone organic and inorganic matrix in newborn rats after maternal application of antiretroviral agents: Indinavir and zidovudine

Abstract: This work presents results concerning influence of indinavir (protease inhibitor, PI(1)) and zidovudine (nucleoside and nucleotide inhibitor of reverse transcriptase, NRTI) administered to pregnant Wistar rat females on organic and mineral constituents of bones and teeth (mandibles, skulls, tibiae, femurs, and incisors) of their offspring at the age of: 7, 14, and 28 days studied by means of induced laser and X-ray fluorescence spectroscopy supported by digital radiography. Influence of indinavir administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The decrease in bone mineral density is one of the most studied adverse effects of prenatal ARV use (Mora et al , ; Amorosa and Tebas, ); however, only one recent study on pregnant rats and their offspring (Maciejewska et al , ) has demonstrated a decrease in calcium ion concentration in bone and teeth, as well as disorders of trace elements, following indinavir administration. Also, a delay in the development of organic dental matrix in teeth of newborn rats of mothers exposed to in utero to zidovudine was demonstrated.…”
Section: Questionsmentioning
confidence: 99%
“…The decrease in bone mineral density is one of the most studied adverse effects of prenatal ARV use (Mora et al , ; Amorosa and Tebas, ); however, only one recent study on pregnant rats and their offspring (Maciejewska et al , ) has demonstrated a decrease in calcium ion concentration in bone and teeth, as well as disorders of trace elements, following indinavir administration. Also, a delay in the development of organic dental matrix in teeth of newborn rats of mothers exposed to in utero to zidovudine was demonstrated.…”
Section: Questionsmentioning
confidence: 99%